Crashworthiness Design for an Electric City Car against Side Pole Impact - Setiawan, Rachman; Salim, Mohammad Rusyad (Journal of Engineering and Technological Sciences, 2017)
Electric vehicles are increasingly popular as an alternative to fossil fuel vehicles. The presence of batteries and electric motors poses different risks in collision accidents. The deformation of the batteries could spark a fire or explosion that in turn could endanger the passengers. The prototype of an Indonesian electric city car is currently being developed, which includes a battery pack located underneath the passenger compartment and electric motors in the front compartment. A crashworthiness design against side pole impact, in accordance with the Euro NCAP standard, was simulated numerically. In order to reduce the risk of battery explosion, an impact energy absorbing structure is proposed for implementation at the sides of the batteries. The structure of the four-passenger hatchback electric city car was modeled using all-shell elements with material properties for common automotive application and analyzed using the finite element method with dynamic plasticity capability. For the preliminary design, the minimum deformation of the batteries that can cause battery explosion was used as the failure criteria. From a number of design alternatives, the use of aluminum foam as impact energy absorber produced sufficient protection for the battery pack against side pole impact, hence effectively reducing the risk to an acceptable limit.